'It is nothing more than a senior moment': the moderating role of subjective age in the effect of change in memory on self-rated memory. (1st February 2019) - Segel-Karpas, Dikla; Palgi, Yuval
ABSTRACT: Objective: The association between memory performance and self-rated memory is yet to be understood. More specifically, little is known about the factors that lie at the base of self-evaluations of memory in relation to actual changes in memory. In this study, we suggest that subjective age modifies the effect of objective change in memory on self-rated memory. Method: We used two waves of the Health and Retirement Study ( N = 4624) to examine whether subjective age moderates the effect of experienced changes in memory between T1 and T2 on self-rated memory at T2. Results: Our results suggest that subjective age is a significant moderator of the effect of change in memory on self-rated memory. The effect is weaker among those with younger subjective age, and stronger for those with older subjective age. Conclusion: While preserving a young subjective age is usually considered an adaptive strategy, it also has potential negative effects, masking changes in memory performance.